2021
DOI: 10.3847/1538-4357/ac0ae0
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the Dust Properties in z ≃ 1–3 Submillimeter Galaxies with ALMA

Abstract: We present Atacama Large Millimeter/submillimeter Array (ALMA) 2 mm continuum observations of a complete and unbiased sample of 99 870 μm selected submillimeter galaxies (SMGs) in the Extended Chandra Deep Field South (ALESS). Our observations of each SMG reach average sensitivities of 53 μJy beam −1 . We measure the flux densities for 70 sources, for which we obtain a typical 870 μm-to-2 mm flux ratio of 14 ± 5. We do not find a redshift dependence of this flux ratio, which would be expected if the dust emiss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 109 publications
(213 reference statements)
8
26
0
Order By: Relevance
“…While the redshift distribution of galaxies selected at 2 mm is expected to be relatively high with 〈z〉 ≈ 3.6 (Casey et al 2021), the selection of these targets at 850 μm leads to a lower median redshift, consistent with what has been previously found for 850 μm-selected DSFGs (e.g., Dudzevičiūtė et al 2020;da Cunha et al 2021). Though we expect the follow up 2 mm observations to filter out lower-redshift sources (Casey et al 2021;Zavala et al 2021;Manning et al 2022), our source selection here is based on 850 μm, and thus for this study the redshift distribution is reflective of the 850 μm DSFG redshift distribution.…”
Section: = -+supporting
confidence: 87%
See 2 more Smart Citations
“…While the redshift distribution of galaxies selected at 2 mm is expected to be relatively high with 〈z〉 ≈ 3.6 (Casey et al 2021), the selection of these targets at 850 μm leads to a lower median redshift, consistent with what has been previously found for 850 μm-selected DSFGs (e.g., Dudzevičiūtė et al 2020;da Cunha et al 2021). Though we expect the follow up 2 mm observations to filter out lower-redshift sources (Casey et al 2021;Zavala et al 2021;Manning et al 2022), our source selection here is based on 850 μm, and thus for this study the redshift distribution is reflective of the 850 μm DSFG redshift distribution.…”
Section: = -+supporting
confidence: 87%
“…To test the impact of SED fitting on our results, we also fit our SEDs using isothermal modified blackbody models as in da Cunha et al (2021). Given the known degeneracies and bias from opacity assumptions, we toggled λ 0 over multiple fits.…”
Section: Emissivity Spectral Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…These efforts have pointed to the need to better understand the properties of dust, and their relationships to metal and gas masses. For example recent measurements of dust mass of SMGs have arrived to an average of about 6 − 7 × 10 8 M (Dudzevičiūtė et al 2020;da Cunha et al 2021), somewhat higher than what is seen in most models. In our forthcoming paper (Liao et al in preparation) we will show that our sample SMGs have even higher dust masses.…”
Section: Discussionmentioning
confidence: 85%
“…Galaxies that are bright in far-infrared and submillimeter host sites of both vigorous star formation and active black hole growth (Sanders et al 1988). Predominantly at z = 1 − 4 (e.g., Chapman et al 2005;Ivison et al 2007;Wardlow et al 2011;Casey et al 2014;Hodge & da Cunha 2020), recent studies focusing on submillimeter galaxies that are bright at 850 µm (S 850 1 mJy), or SMGs, found that they are some of the most massive systems during these epochs, sitting at the massive end of the stellar mass functions (Dye et al 2008;Hainline et al 2011;Micha lowski et al 2012;Koprowski et al 2016;Dudzevičiūtė et al 2020), molecular gas mass functions (Bothwell et al 2013;Birkin et al 2021), dust mass functions (da Cunha et al 2015(da Cunha et al , 2021, and also the halo mass functions (Hickox et al 2012;Chen et al 2016;Wilkinson et al 2017;An et al 2019;Stach et al 2021). The large cold molecular gas reservoir (∼ 10 11 M ) estimated from their molecular line measurements is believed to provide the gas supply over ∼100 Myr timescales for their extensive starformation rates (SFRs) of ∼100-1000 M yr −1 , similar to the levels of star formation seen in nearby (hyper-)ultra-luminous infrared galaxies (HyLIRGs/ULIRGs; Sanders & Mirabel 1996).…”
Section: Introductionmentioning
confidence: 99%